A Biomechanical Comparison of Three Miniature Locking Plate Systems in a Rabbit Radial and Ulnar Fracture Model - Takizawa, Harue; Honnami, Muneki; Sakai, Takamasa; Sasaki, Akari; Sakamoto, Ayumi; Mochizuki, Manabu (Veterinary and Comparative Orthopaedics and Traumatology, 2019)
Objective The aim of this study was to evaluate the biomechanical properties of three different miniature locking plate systems used to fixate radial and ulnar fractures in toy breed dogs. Implant size, shape, material and locking systems differ, and their influence on the fracture healing process is unknown. In the present study, we aimed to investigate this matter in vivo using rabbit radial and ulnar fracture models.Study Design Eighteen rabbits were randomly divided into three groups, and the left radius and ulna were osteotomized to create fracture models. The osteotomies were then fixated using either the TITAN LOCK 1.5, Fixin micro or LCP 1.5 system. Radiographs were obtained 2, 3 and 4 weeks after surgery. Four weeks after surgery, the radiuses were collected and used for biomechanical testing or histological examinations.Results During the 4 weeks of observation, no adverse effects due to the implants occurred. The radiographic scores in each group did not differ significantly at any time point. The maximum load in the LCP group was significantly higher than that in the TITAN and Fixin groups. There was no significant difference in bending stiffness or work to failure among the groups. Initial fracture healing via woven bone was evident at histological evaluation.Conclusions All three miniature locking plate systems provided adequate fracture stabilization 4 weeks after surgery, despite their differences, in rabbit models.
Keywords: miniature locking plate; fracture repair; rabbit fracture model; biomechanical comparison; toy breed dogs